Analysis of Students' Mathematical Literacy Ability on High-Level Problems of PISA viewed from Gender - Niakmatul Husni; Tatang Herman (Universitas Syiah Kuala, 2024)
According to the 2022 PISA study, the mathematical literacy abilities of Indonesian students remain notably low, with fewer than 1% achieving proficiency levels between 4 and 6. This research employs qualitative methodologies to explore students' mathematical literacy in addressing high-level PISA problems, specifically examining gender-based differences within the context of number pattern topics. The study involved 34 grade VIII students from a public junior high school in Bandung, comprising 16 male and 18 female participants. Data were gathered through the administration of mathematical literacy tests and supplemented by in-depth interviews conducted with teachers and students. The results indicate that students' mathematical literacy is generally weak, largely attributed to their lack of familiarity with solving complex problems and difficulties in progressing beyond identifying initial patterns. Furthermore, the analysis revealed that female students outperformed their male counterparts in tackling high-level PISA problems. To enhance students' mathematical literacy, the study advocates for integrating high-level problems into the learning process. Such integration is anticipated to foster improvements in mathematical literacy, alongside the necessity for schools to implement an operational curriculum prioritising the reinforcement of foundational materials essential for developing this competency.